Personal values in an acculturation context: a study of Filipina women in Rome - Podio-Guidugli, Sara; Suta, Joana; Vecchione, Michele; Barbaranelli, Claudio (INYI Journal, 2012)
The current context of global migration trends and the new realities of multicultural societies make clear the need for understanding the role that personal values can have on immigrants’ acculturation attitudes. This study highlights the adaptive role of values such as benevolence, conformity, and security in a sample of Filipina mothers who immigrated to Rome (Italy) with their families. These initial results can be useful for future studies and interventions policies focused on immigrants’ well-being.